It’s Just a Phase: Exploring the Relationship Between mRNA, Biomolecular Condensates, and Translational Control - Parker, Dylan M.; Winkenbach, Lindsay P.; Osborne Nishimura, Erin (Frontiers in Genetics, 2022)
Cells spatially organize their molecular components to carry out fundamental biological processes and guide proper development. The spatial organization of RNA within the cell can both promote and result from gene expression regulatory control. Recent studies have demonstrated diverse associations between RNA spatial patterning and translation regulatory control. One form of patterning, compartmentalization in biomolecular condensates, has been of particular interest. Generally, transcripts associated with cytoplasmic biomolecular condensates - such as germ granules, stress granules, and P-bodies - are linked with low translational status. However, recent studies have identified new biomolecular condensates with diverse roles associated with active translation. This review outlines RNA compartmentalization in various condensates that occur in association with repressed or active translational states, highlights recent findings in well-studied condensates, and explores novel condensate behaviors.